2010
DOI: 10.5152/jtgga.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of nuchal translucency and serum markers for down syndrome screening with ductus venosus Doppler measurements in the first trimester

Abstract: Objective:The aim of the study was to improve nuchal translucency (NT) and serum marker Down syndrome (Tri21) screening methods by including fetal ductus venosus (DV) Doppler measurements. Material and Methods:A total of 213 pregnant women were screened consecutively by combining maternal age, fetal NT and maternal serum pregnancy associated plasma protein A (PAPP-A) and free β-human chorionic gonadotropin (f β-HCG) values at 11-14 weeks of gestation. Also, a DV Doppler analysis was performed for the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…Also, in pregnant women recommended first trimester combined screening test by adding combined test into the clinical use, it is seen that the rate of pregnant women accepting procedure increases significantly. [4] In the studies carried out in Turkey, [5,6] mean f-βhCG values were reported between 0.82 and 1.07 MoM and mean PAPP-A values were reported between 1.06 and 1.61 MoM. In our study group, we found these values as 1.25 and 1.16 MoM, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…Also, in pregnant women recommended first trimester combined screening test by adding combined test into the clinical use, it is seen that the rate of pregnant women accepting procedure increases significantly. [4] In the studies carried out in Turkey, [5,6] mean f-βhCG values were reported between 0.82 and 1.07 MoM and mean PAPP-A values were reported between 1.06 and 1.61 MoM. In our study group, we found these values as 1.25 and 1.16 MoM, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, impaired endothelial development and differentiation and lymphatic abnormalities have been reported to play a role in the disorder. In a study by Özlem et al, [16] maternal age, nuchal translucency, DV Doppler findings were examined in 213 pregnant women between 11-14 gestational weeks. DV PI was >95 p in 12 of 213 patients and in fetuses of two of these pregnants IUGR was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, cuando el aumento del valor de la TN está asociado a pérdida o inversión de la onda A en la ecografía doppler venosa, el riesgo de CC aumenta aún más (60,61). Por tanto, en estos fetos, la suma de la evaluación doppler venosa, puede mejorar la precisión de la predicción de CC (62).…”
Section: Malformaciones Congénitasunclassified